ШАЙЫР РАУФ ПАРФИЙДИӉ АРАЛЫҚ ФОРМАСЫНДАҒЫ ҚОСЫҚЛАРЫНЫӉ ӨЗИНЕ ТӘН ӨЗГЕШЕЛИКЛЕРИ - Гайлыева, О.К. (ILIM hám JÁMIYET, 2020)
This article explores the work of the famous Uzbek poet Rauf Parphiy, especially the extraordinary poems of the poet in frontier forms. The artistic mastery of the poet’s creativity is revealed in a comparative form on the basis of his free songs.